The Impact of Economic Freedom on State Legitimacy An Empirical Investigation - Hindermann, Christoph Michael (Wirtschaft und Politik,, 2018)
Christoph Michael Hindermann uses a statistical approach to analyze the impact of economic freedom on state legitimacy. Based on multiple regression models, the author not only extracts the determinants of legitimacy but also shows that rule of law is the most important area of economic freedom for legitimacy. In addition, the results also indicate that democracies are not necessarily more legitimate than autocracies and that wealthier countries are, ceteris paribus, perceived as less legitimate. Due to the strong quantitative approach, this thesis contributes not only to the political theory of liberalism and to the field of institutional economics but also enriches the debate on how a legitimate state ought to be. Contents The Concept of Legitimacy Legitimacy and its Measurement The Determinants of Legitimacy Economic Freedom and Legitimacy Target Groups Scholars and students of economics, political science, and sociology Politicians, publicists and executives in higher service About the Author Christoph M. Hindermann is research associate at the institute of institutional economics and economic policy at the University of Erfurt.